KINERJA KEUANGAN BERDASARKAN PROSES BISNIS INTERNAL PERUSAHAAN DENGAN METODE BALANCED SCORECARD PADA PERUSAHAAN BERBAGAI SEKTOR DENGAN KAPITALISASI TERTINGGI DI BURSA EFEK INDONESIA TAHUN 2020-2021 - Listyani, Th. Tyas; Nisak, Novi Meherizca Choirun; Prihatiningsih, Prihatiningsih (KEUNIS, 2023)
This study aims to analyze financial performance based on the company's internal business processes using the balanced scorecard method in various sector companies with the highest capitalization on the Indonesia Stock Exchange which experienced a decline in profits in 2020-2021. This research design is a descriptive applied quantitative research with ASII, BBCA, and TLKM samples. The analytical method used is the Balanced Scorecard Method with four perspectives. The results of the analysis show that ASII 2020 results in a final total score of 50% in the BBB category and unhealthy conditions, ASII 2021 at 57% in the BBB category and unhealthy conditions, BBCA 2020 at 62% in the BBB category and unhealthy conditions, BBCA 2021 by 74% with category A and very healthy condition, TLKM 2020 by 58% with category BBB and unhealthy conditions, and TLKM 2021 by 71% with category A and very healthy condition.